First take 6a^2b^3+12a^4b
Identify the common variables to both 6a^2b^3 and 12a^4b
In this case a^2 and b is a common variable. So by dividing by both terms we get a^2b(6b^2 + 12a^2).
However we now have to look at the common factors for both terms which is 6. By dividing further still we get a final answer of:
6a^2b(b^2+2a^2)
6a^2b^3+12a^4b
=we will take the common variables to out.
6a^2b(b^2+2a^2)
your question is not written clearly following the usual conventions of syntax that a2= a x 2 = 2 x a = 2a.
For example your question can be interpreted as follows
6a2b3 +12a4b = (6 x a x 2 x b x 3) + (12 x a x 4 x b ) = 36 ab + 48 ab = 84 ab
alternatively
6a ^2 x b ^3 + 12 a ^4 x b . In this expression there are two terms. For factorizing we need to identify the highest common factor (HCF) between them.
For each of the constant terms , and pronumerals, a and b, we will identify the HCF .
For the constants 6 and 12 the HCF is 6.
For a, the HCF between the two terms is a^2
Between b ^3 and b , the HCF is simply b.
Collecting all the HCFs , we write the factors as
6 a^2 b .
If we take out the combined HCF from the expression we will obtain
6 a^2 b ( b^2) = 6 a^2 b^3 which is the first term of the expression
6 a^2 b (2a^2) = 12 a^4 b, the second term of the expression.
finally , the factorization results in:
6a^2 b^3 + 12 a^4 b = 6a^2 b ( b^2 + 2 a^2)
6a^{2}b(b^{2}+2a^{2})
First multiply the numbers together: 6x2x3= 36 and 12x4= 48
Then multiply the a and b which is ab.
Then put everything together to get: 36ab+48ab= 84ab
first we multiply all the terms
= 6 x a x 2 x b x 3 + 12 x a x 4 x b
= 36ab + 48ab
= 84 ab Answer.